Unlocking the connection: hemoglobin glycation index as a key driver of bone loss in diabetes-related osteoporosis - Wen, Zhangxin; Liu, Xinpeng; Jin, Wanlin; Sheng, Zhi-Feng; Liu, Hong (Frontiers in Endocrinology, 2025)
BackgroundOsteoporosis, marked by decreased bone density and heightened fracture risk, is prevalent in aging individuals with type 2 diabetes mellitus (T2DM). The hemoglobin glycation index (HGI), a novel biomarker for glycation status, reflects advanced glycation end products (AGEs) accumulation. However, its role in bone metabolism and osteoporosis development remains poorly understood.MethodsWe enrolled 412 hospitalized T2DM patients to investigate the relationship between HGI and vertebral bone mineral density (BMD). BMD was measured by dual-energy X-ray absorptiometry (DXA), and bone turnover markers (PINP, β-CTX, OC) were evaluated. Correlation analyses were conducted to explore the associations between HGI, BMD, and bone cell activity markers. Mediation analysis was performed to determine whether osteoclast activity mediated the relationship between HGI and vertebral BMD.ResultsPatients with vertebral fractures exhibited significantly higher HGI levels compared to those without fractures (0.8 ± 2.1 vs. 0.3 ± 2.1, respectively). A negative correlation was observed between HGI and vertebral BMD (r = -0.140, p = 0.005), while HGI showed a positive correlation with CTX (r = 0.15, p = 0.03). No significant association was found between HGI and P1NP (r = 0.022, p = 0.755). Mediation analysis revealed that osteoclast activity accounted for 28.88% of the relationship between HGI and vertebral BMD. Further subgroup analysis by age (<65 and ≥65 years) indicated that the association between HGI and vertebral BMD was stronger in patients aged ≥65 years, suggesting age-related differences in the HGI-osteoporosis relationship.ConclusionThis study demonstrates that HGI contributes to bone loss and reduced vertebral BMD by enhancing osteoclast activity. While the impact of HGI on osteoblast function remains unclear, its significant influence on bone resorption highlights its potential role in the pathogenesis of osteoporosis in T2DM patients. These findings offer novel insights into the relationship between diabetes and osteoporosis and suggest that managing HGI levels may provide a therapeutic target for preventing osteoporosis and fractures in T2DM patients.